Study on influence of flow rates on voids in waxy crude oil subjected to dynamic and static cooling - Chala, G.T. (Universiti Malaysia Pahang, 2015)
The assumption of constant yield stress in the conventional restart pressure equation neglects the effects of thermal shrinkage and gas voids formation, which in turn resulted in an over-designed production piping systems. This paper presents a study on the effects of flow rates on the formation of voids in gelled waxy crude oil. A flow loop rig simulating offshore waxy crude oil transportation was used to produce a gel. A Magnetic Resonance Imaging (MRI) was used to scan the gelled crude oil over the three planes. Waxy crude oil underwent both dynamic and static cooling to observe the effects of volume flow rates on the voids formed in wax-oil gel. Volume flow rate was found to have different influences on the intra-gel voids in the pipeline. A volume flow rate of 5 L/min resulted in a maximum total voids volume of 6.98 while 20 L/min produced a minimum total voids volume of 5.67 in the entire pipe. Slow flow rates resulted in a larger voids volume near the pipe wall. In contrast, faster flow rates produced insignificantly higher voids volume around pipe core. Generally, slower flow rates favoured the formation of higher total voids volume following sufficient steady time of wax crystal formation, producing larger voids areas in gelled waxy crude oil. Â© 2015 Universiti Malaysia Pahang, Malaysia.